(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2024)
The subscription economy has emerged as a transformative force reshaping traditional business models across industries. This article explores the rise of the subscription economy and its impact on businesses, consumers, and the broader economy. It delves into the key drivers behind the growth of subscription-based models, including changing consumer preferences, advancements in technology, and the shift towards recurring revenue streams. Additionally, the article examines the benefits and challenges of subscription-based business models for both businesses and consumers, as well as the implications for market competition, customer relationships, and innovation. By analyzing case studies and industry trends, this article provides insights into how organizations can adapt to and thrive in the subscription economy landscape.